Effects of Moisture Absorption and Thickness Swelling Behaviors on Mechanical Performances of Carica Papaya Fiber Reinforced Polymeric Composites. Issue 15 (23rd November 2022) - Saravanakumaar, A.; Senthilkumar, A.; Muthu Chozha Rajan, B.; Rajini, Nagarajan; Ismail, Sikiru O.; Mohammad, Faruq; Al-Lohedan, Hamad A.
ABSTRACT: In this study, composite materials were made from Carica papaya fibers (CPFs), as a reinforcing element in polypropylene (PP), polyester (P) and epoxy (E) matrices, using compression molding technique. Experiments were conducted to evaluate the input parameters with their output responses, specifically density and thickness. Various CPF reinforced PP, P, and E composite specimens with varied fiber orientations of 0°, 45°, and 90° as well as percentages of fiber contents of 10, 20, and 30 wt.% were prepared, according to the ASTM D 570 standard. From the results obtained, it was observed that CPF/E composites with fewer fraction of CPF and orientation of 90° exhibited less water absorption throughout the whole duration of immersion. Water saturated CPF/E composite specimen, designated as E8, with orientation of 0° and fiber content of 20 wt.% showed the highest tensile, flexural strengths, and Shore D Hardness of 119, 115 MPa, and 85, respectively. Also, CPF/E composite specimen (E7) with 90° and 10 wt.% recorded the lowest tensile strength of 32 MPa, and CPF/E composite (E3) with 90° and 30 wt.% showed the lowest flexural strength of 41 MPa. Hence, it was evident that optimum CPF reinforced polymeric composite can be used for some outdoor engineering applications.